Generation and evaluation of anti-mouse IgG IgY as secondary antibody. Issue 8 (1st September 2020) - Zhang, Qi; He, Dongyang; Xu, Long; Ge, Shikun; Wang, Jinquan; Zhang, Xiaoying
Abstract: In order to evaluate the possibility of using IgY as the secondary antibody in immunoassay, specific IgY (1: 128, 000) was generated by immunizing hens with mouse serum IgG purified by protein A column. IgY was extracted from egg yolk by polyethylene glycol 6000 (PEG-6000), and further purified using protein M affinity chromatography column. The purified IgY was conjugated with horseradish peroxidase (HRP) and fluorescein isothiocyanate (FITC), in that order. The reactivity of conjugated antibodies was evaluated by ELISA, Western blot and Immunofluorescence, demonstrating that the obtained IgY was able to conjugate with enzymes, react with mouse primary IgG antibody, and subsequently amplify the antigen-antibody signals in different immune reaction conditions, in a comparable secondary effect to conventional goat anti-mouse IgG antibody. The obtained conjugated antibodies showed high stability in broad pH ranges (4–10; >70%) and high thermostability at 37 °C for 84 h (>85%). Despite the need to further consider and evaluate the industrial standardization and production process, our data provided the primary evidence that conjugated IgY antibodies can be used as a secondary antibody for broad immunological analysis.